2015
DOI: 10.1371/journal.pbio.1002281
|View full text |Cite
|
Sign up to set email alerts
|

Live Fast, Die Young: Experimental Evidence of Population Extinction Risk due to Climate Change

Abstract: Evidence has accumulated in recent decades on the drastic impact of climate change on biodiversity. Warming temperatures have induced changes in species physiology, phenology, and have decreased body size. Such modifications can impact population dynamics and could lead to changes in life cycle and demography. More specifically, conceptual frameworks predict that global warming will severely threaten tropical ectotherms while temperate ectotherms should resist or even benefit from higher temperatures. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
173
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 84 publications
(105 reference statements)
9
173
2
8
Order By: Relevance
“…We used the relative changes in abundance to determine the IUCN status of each population, and we identified two populations extremely at risk, one population at risk and 11 nonthreatened populations (Supporting Information Table S1). This classification is consistent with the predictive model of climate change effect on population trends derived from a previous field experiment (Bestion et al., ). We managed to sample 135 individuals from those populations in a critical state, and it is worth noting that studies including as many individuals from collapsing populations are rare and urgently needed.…”
Section: Methodssupporting
confidence: 89%
“…We used the relative changes in abundance to determine the IUCN status of each population, and we identified two populations extremely at risk, one population at risk and 11 nonthreatened populations (Supporting Information Table S1). This classification is consistent with the predictive model of climate change effect on population trends derived from a previous field experiment (Bestion et al., ). We managed to sample 135 individuals from those populations in a critical state, and it is worth noting that studies including as many individuals from collapsing populations are rare and urgently needed.…”
Section: Methodssupporting
confidence: 89%
“…This could have important consequences for the resilience of ecosystems, because fast life cycles are hypothesized to promote rapid rates of population growth, and hence instability (Bestion et al, 2015). Moreover, accelerated life history responses were observed only under high levels of food abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Warmer temperatures can advance reproductive maturation, increase reproduction frequency and shorten life span, leading to an accelerated life cycle (Bestion, Teyssier, Richard, Clobert, & Cote, 2015). Warmer temperatures can advance reproductive maturation, increase reproduction frequency and shorten life span, leading to an accelerated life cycle (Bestion, Teyssier, Richard, Clobert, & Cote, 2015).…”
mentioning
confidence: 99%
“…In the context of current climate change, the positive effect of temperature might have important consequences for common lizards' population dynamics. For example, Bestion et al [17] experimentally demonstrated a switch of demographic strategies in a warming experiment conducted in semi-natural conditions. Their results showed that warmer temperatures led to an accelerated pace of life (e.g.…”
Section: Discussionmentioning
confidence: 99%